MODULE IN PREPARING STUDENTS FOR PROFESSIONAL ACTIVITY USE OF TEACHING TECHNOLOGIES - Usmonova, Umida (Maktabgacha taʼlim jurnali, 2022)
The article discusses modular educational technologies, the importance of their use in the higher education system and the content of preparing students for professional activities.